A thieno[2,3-d]pyrimidine scaffold is a novel negative allosteric modulator of the dopamine D2 receptor - Fyfe, Tim J.; Zarzycka, Barbara; Lim, Herman D.; Kellam, Barrie; Mistry, Shailesh N.; Katrich, Vsevolod; Scammells, Peter J.; Lane, J. Robert; Capuano, Ben (American Chemical Society, 2018)
Recently, a novel negative allosteric modulator (NAM) of the D 2-like dopamine receptors 1 was identified through virtual ligand screening. This ligand comprises a thieno[2,3-d]pyrimidine scaffold that does not feature in known dopaminergic ligands. Herein, we provide pharmacological validation of an allosteric mode of action for 1, revealing that it is a NAM of dopamine efficacy and identify the structural determinants of this allostery. We find that key structural moieties are important for functional affinity and negative cooperativity, whilst functionalization of the thienopyrimidine at the 5- and 6-positions results in analogues with divergent cooperativity profiles. Successive compound iterations have yielded analogues exhibiting a 10-fold improvement in functional affinity, as well as enhanced negative cooperativity with dopamine affinity and efficacy. Furthermore, our study reveals a fragment-like core that maintains low μM affinity and robust negative cooperativity with markedly improved ligand efficiency.